2018
DOI: 10.1016/j.heliyon.2018.e00748
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic abatement of CO species from incomplete combustion of solid fuels used in domestic cooking

Abstract: This study reveals a first time approach to catalytic based interventions primarily on indoor air pollution emanating from commercial and household solid fuel burning in a region in Nigeria. An intensive survey of the temperatures at different locations in the common stoves used for cooking was conducted so as to ascertain temperatures suitable for catalyst efficiency and stability. Furthermore, cobalt and iron based catalysts were prepared using ultra stable Y type zeolite as supports. The synthesized catalys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…The purpose of measurement of the dimensions of the slot was to compare the deposits in the spent CC with the new CC. The EDS results revealed that the primary elements present in the ceramic bed were O, Al, Si, Mg, Na, C, Pt, Pd, Rh, and C. The results are in accordance with the standard composition of an oxidation-reduction CC [24]. In theoretical scenarios, combustion of hydrocarbon fuel should produce CO 2 and H 2 O, but in actual conditions, the combustion process is oxygen deficient, resulting in the production of harmful pollutants such as carbon monoxide (CO), unburned hydrocarbons, and oxides of nitrogen and sulfur [25].…”
Section: Resultssupporting
confidence: 83%
“…The purpose of measurement of the dimensions of the slot was to compare the deposits in the spent CC with the new CC. The EDS results revealed that the primary elements present in the ceramic bed were O, Al, Si, Mg, Na, C, Pt, Pd, Rh, and C. The results are in accordance with the standard composition of an oxidation-reduction CC [24]. In theoretical scenarios, combustion of hydrocarbon fuel should produce CO 2 and H 2 O, but in actual conditions, the combustion process is oxygen deficient, resulting in the production of harmful pollutants such as carbon monoxide (CO), unburned hydrocarbons, and oxides of nitrogen and sulfur [25].…”
Section: Resultssupporting
confidence: 83%
“…Therefore, range hoods, chimneys, and natural ventilation methods can provide limited improvements. Currently, there are various technologies for removing harmful cooking-induced emissions, such as activated carbon filter adsorption, high-efficiency particulate air (HEPA) filters and electrostatic precipitators (ESPs) [ [19] , [20] , [21] , [22] , [23] ]. The best way to improve IAQ is by reducing source emissions by using better fuel sources, cooking methods, and cooking oils.…”
Section: Introductionmentioning
confidence: 99%
“…These enhance the air circulation around the fuel improving the air-to-fuel ratio hence reducing the combustion emissions, as well as drawing out any released pollutant through the stack. Other stoves use a catalyst layer/mesh just above the solid fuel [11] to oxidise the toxic emissions during combustion while other fix the catalyst mesh in the stack of an improved cookstove [12] for the same purpose.…”
Section: Introductionmentioning
confidence: 99%